ZAKAT FOR POVERTY ALLEVIATION AND INCOME INEQUALITY REDUCTION: WEST JAVA, INDONESIA - Ayuniyyah, Qurroh; Pramanik, Ataul Huq; Saad, Norma Md.; Ariffin, Muhammad Irwan (Journal of Islamic Monetary Economics and Finance, 2018)
This research aims to analyze the role of zakat distribution programs for poverty allevation and income inequality reduction among groups in urban and rural areas. It takes the case study of 1,309 zakat beneficiaries managed by the National Zakat Board of Indonesia (BAZNAS) as the coordinating zakat institution in Indonesia, in five different cities and regencies in West Java Province namely, Bogor, Depok and Sukabumi. The analytical tools used in this study are the modification of the Center of Islamic Business and Economic Studies (CIBEST) model, CHAID analysis, Deciles method and Gini coefficient. This study suggests that the present zakat distribution programs can significantly alleviate poverty and reduce income inequality among the observed zakat beneficiaries. It is also found that spiritual supervision and routine assistance form BAZNAS officers, informal education, family size, age and job of the respondents are the variables that are statistically significant in influencing the increase of the households’ monthly income and spirituality.